Water Pipeline Network Analysis Of Usm Engineering Campus Using Watergems - Salleh, Nurhafizah Abdul (Universiti Sains Malaysia, 2022)
The complexity of water pipeline networks is managed using hydraulic models. Utilising the WaterGEMS model, the pressure, flow velocity, and head loss of the USM Engineering Campus pipeline network was estimated. The WaterGEMS model includes 9.882 km pipelines, 132 nodes (52 demand nodes) that spread over 34 different types of buildings, and a tapping point where outflow starts. The pipeline network analysis reveals that 43.6% of the flow velocity in the pipeline does not meet the allowable, minimum, or maximum velocities, and 3.8% of the nodes do not meet the minimum residual pressure. Thus, it causes exceedingly high head losses. Optimisation of the pipeline network had been done to the least-cost design by reducing the pipe diameters. A comparison of results showed that in the optimised networks, 100% of the nodes reached the minimum allowable pressure, which is 15 meters above the platform level of a building, without the use of a pump. 87.9% of pipelines achieve the allowed minimum and maximum velocity. Lastly, costs for energy consumption due to pump operation are discussed. The bill calculation results show that in the USM Engineering Campus, the total consumption rate of pumps for one month is RM 121,026.43. For one year, it is RM 1,452,317.16, contributing to 28.01% of the overall total usage of electricity. Thus, electricity consumption by pump operation is considered high, making it one of the dominant costs in USM Engineering Campus's pipeline network. Overall, the finding of this study indicated that by optimisation of pipe size, pipeline expenses can be reduced with the satisfaction of required velocity and residual pressures. Other than pipeline expenses, electricity consumption by pump operation is one of the highest marginal costs for water utilities at USM Engineering Campus.